The impact of teachers' characteristics on their self-efficacy and job satisfaction: A perspective from teachers engaging students with disabilities - Shaukat, S.; Vishnumolakala, Venkat Rao; Al Bustami, G. (2019)
The study investigated the impact of Pakistani special education teachers' characteristics like gender, age, background qualification, teaching experience and professional qualification on their self-efficacy beliefs and job satisfaction. The study employed a quantitative research design comprising 94 female and 24 male teachers from five public schools located in the district of Lahore. The findings from self-efficacy and job satisfaction measures indicate that teachers' characteristics like gender, age, academic education and teaching experience had significant influence on self-efficacy beliefs and job satisfaction. Female teachers exhibited higher level of self-efficacy beliefs and job satisfaction to teach students with diverse needs as compared with their male counterparts. However, a significant correlation between self-efficacy and job satisfaction was not found. This study suggests professional training programs tailored to enhance male and female teachers' self-efficacy beliefs and job satisfaction while addressing the needs of children with disabilities.